Changes in the normal appearing white-gray matter and cognitive impairment in clinically isolated syndrome [Klinik izole sendromlarda normal görünümlü beyaz-gri cevherdeki değişiklikler ve kognitif etkilenim] - (:unkn) unknown (Ege University Press, 2015)
Background and purpose: To assess the normal appearing white and grey matter changes in clinically isolated syndrome (CIS) patients and their correlations if present to neurocognitive tasks. Those changes can be revealed by magnetization transfer imaging (MTI) and Diffusiontensor magnetic imaging (DTI) technique. Methods: Diffusion-tensor magnetic and magnetization transfer imaging measurements at normal appearing left-right dorsolateral prefrontal cortex, right-left anterior cingulate gyrus, corpus callosum genu-splenium were made. In order to assess whether or not the cognition was affected following neurocognitive tests [Wisconsin Card Sorting Test (WCST), California Verbal Learning Test (CVLT), Stroop Test(ST), Digit Range (DR) and the Paced Auditory Serial Addition Test (PASAT)] were performed. Results: Patients were found to have a lower fractional anisotropy (FA) compared the controls in the left dorsolateral prefrontal cortex at DTI technique. Neurocognitive assessment showed that patients did not perform well in WCST, CVLT, ST, DR. Results were associated with abnormal FA in the left dorsolateral prefrontal cortex. Conclusions: Results showed the presence of deficits of executive function such as attention, working memory, strategy formulation, and monitoring ongoing mental activity and speeded information processing in CIS patients. These findings suggest that early cortical changes can be seen even in CIS patients and responsible for early neurocognitive impairments. © 2015, Ege University Press. All rights reserved.
Keywords: Clinically isolated syndrome; Cognition; Normal appearing white-grey matter